The Effect of Simulated Rain on the Activity and Uptake of Imazapyr on Mikania micrantha H.B.K. - Ipor, Isa; Price, C. E. (1992)
The effect of simulated rain on the activity and uptake of imazapyr was studied on Mikania micrantha H.B.K. The activity of imazapyr was significantly increased both at high concentration of imazapyr and low volumes of spraying. Imazapyr 1-equired at least six hrnlTS between herbicide application and onset of simulated rain to obtain more than 50% control. Increasing the volume and intensity of simulated rain adversely affected the activity of imazapy1-. Lowest percentage of control was obtained at 10 mm and 50 mm/h for volume and intensity of simulated rain respectively. Greater uptake of l~C-imazapyr was recorded in plants pretreated with simulated rain than those without expomre to simulated rain. Twenty four hours after treatment, uptake was 78.7% and 70.5 % for those exposed to simulated rain and without simulated min respectively.